2016
DOI: 10.1016/j.actbio.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Titanium surface characteristics, including topography and wettability, alter macrophage activation

Abstract: Biomaterial surface properties including chemistry, topography, and wettability regulate cell response. Previous studies have shown that increasing surface roughness of metallic orthopaedic and dental implants improved bone formation around the implant. Little is known about how implant surface properties can affect immune cells that generate a wound healing microenvironment. The aim of our study was to examine the effect of surface modifications on macrophage activation and cytokine production. Macrophages we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
431
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 538 publications
(460 citation statements)
references
References 34 publications
25
431
2
2
Order By: Relevance
“…[10][11][12] Although rapid physiological resolution of inflammation is conducive to tissue healing, continued chronic inflammation would result in the hyperplasia of fibrotic scar tissue, ultimately leading to implant failure. 13,14 Therefore, it would also be beneficial for early tissue healing and implant success to control the inflammatory process through macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Although rapid physiological resolution of inflammation is conducive to tissue healing, continued chronic inflammation would result in the hyperplasia of fibrotic scar tissue, ultimately leading to implant failure. 13,14 Therefore, it would also be beneficial for early tissue healing and implant success to control the inflammatory process through macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the insufficient new bone formation is observed due to necrosis of hard and soft tissues that result in the implant loosening and subsequent failure [11,12]. The titanium implant surface shape and chemical composition have also been studied to enhance osseointegration, decrease necrosis and prevent inflammation [13][14][15][16][17][18][19][20][21]. Titania nanotubes, formed by anodic oxidation, are a candidate method for the modification of the surface of titanium implants to enhance bone formation function.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, surfaces containing polar groups (COOH and NH 2 ) display an enhanced activity of integrins, which leads to a higher adhesion and spreading of fibroblast cells (Faucheux et al 2004). Using macrocrophage cultures, Hotchkiss et al (2016) observed that materials with high surface wettability produced an antiinflammatory microenvironment through activation of macrophages and the production of cytokines, indicating it is crucial to control wettability when attempting to improve the healing response to biomaterials.…”
Section: Why Modify An Implant Surface?mentioning
confidence: 99%